2020
DOI: 10.7717/peerj.10423
|View full text |Cite
|
Sign up to set email alerts
|

Fungal survival under temperature stress: a proteomic perspective

Abstract: Background Increases in knowledge of climate change generally, and its impact on agricultural industries specifically, have led to a greater research effort aimed at improving understanding of the role of fungi in various fields. Fungi play a key role in soil ecosystems as the primary agent of decomposition, recycling of organic nutrients. Fungi also include important pathogens of plants, insects, bacteria, domestic animals and humans, thus highlighting their importance in many contexts. Tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 103 publications
(139 reference statements)
2
22
0
Order By: Relevance
“…Chemicals and physical parameters affect microbial growth and, in the case of yeasts, the availability of nutrients, as well as temperature and pH, can affect the development of cells. In the presented investigation, the temperature played a key role in the growth ability of Z. obscura LS31012019 which reached its optimum at 25 °C, thus showing the typical feature of mesophilic fungi, which have T opt of 25 − 30 °C and generally tolerate a wider range of temperatures and related stress (Abu Bakar et al 2020 ). Fungal adaptation to variable temperatures implicates alterations in the utilization of many metabolic pathways to compensate for the amount of energy needed in delivering the stress response.…”
Section: Discussionmentioning
confidence: 77%
“…Chemicals and physical parameters affect microbial growth and, in the case of yeasts, the availability of nutrients, as well as temperature and pH, can affect the development of cells. In the presented investigation, the temperature played a key role in the growth ability of Z. obscura LS31012019 which reached its optimum at 25 °C, thus showing the typical feature of mesophilic fungi, which have T opt of 25 − 30 °C and generally tolerate a wider range of temperatures and related stress (Abu Bakar et al 2020 ). Fungal adaptation to variable temperatures implicates alterations in the utilization of many metabolic pathways to compensate for the amount of energy needed in delivering the stress response.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, KEGG enrichment analysis shows the deletion of MoSch9 repressed the production of secondary metabolites that are the key factors in the long-term survivability of any living organism and act as a signaling molecule during various stress conditions [ 78 , 79 , 80 ]. Similarly, the KEGG enrichment analysis and Gene Ontology (GO) in ΔMoSch9 strains at 10 °C revealed that a large number of proteins involved in energy metabolism pathways, in ABC transport, in part of cell wall and membrane, and cellular homeostasis were downregulatedMetabolic pathways are one of the main components that are crucial for energy regulation of the cell and hence for cell survival [ 81 ], and MoSch9 deletion resulted in the disruption of carbohydrate metabolic pathways, which is in accordance with the mutant’s compromised growth during cold stress. In addition, fungal ABC transporters have been previously reported to work as an efflux pump to move natural toxins or cytotoxic secondary metabolites [ 34 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, C. thermophilum mycelium was ground by liquid nitrogen, followed by charging the powders into a centrifuge tube (5 mL) and sonicating thrice on ice with an ultrasonic processor (Scientz, Ningbo, China) in a lysis buffer [including 1% Triton X-100, 10 mM dithiothreitol (DTT), 1% protease inhibitor cocktail, 50 μM PR-619, 3 μM TSA, 50 mM NAM, and 2 mM EDTA] ( Abu Bakar et al, 2020 ). Upon adding an equivalent volume of Tris-saturated phenol (pH 8.0), the resulting mixture was vortexed for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…High-temperature adaptation has attracted widespread attention. The latest review gave an overview and summary of fungal proteomics under temperature stress ( Abu Bakar et al, 2020 ). The 2D protein gels of Friedmanniomyces endolithicus shows that the amount of protein decreases under high-temperature pressure, indicating a lack of heat shock response ( Tesei et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%